Pengaruh Kepemimpinan, Budaya Organisasi, Disiplin Kerja, Motivasi Kerja dan Komitmen terhadap Kinerja Aparatur Sekretariat Daerah Kabupaten Boyolali - Andriyani, Lilis; , Fatchan Achyani, SE, M.Si., Dr. r. (2017)
The research purpose to analysis leadership, the culture of organization, discipline, motivation and commitmen to job performance at Apparatus Secretary's Government of Boyolali Regency. This research uses quantitative method with primary data by questionnaire. Population of this research is employees Apparatus Secretary's Government of Boyolali Regency. Sum samples are 100 respondents. Collecting sample method uses convinence sampling technique. Analysis tools uses validity and realibility test, normality test, multicolineary test, heteroscedasticity, regression linier test, F test, coefficient determination R² test and t test. Abstract Base on analysis data result conclussion variable leadership, culture of organization and motivation is significant influences to job performance of employees Apparatus Secretary's Government of Boyolali Regency. While discipline and commitmen variable is not significant influence to job performance of employees Apparatus Secretary's Government of Boyolali Regency.. Keyword : leadership,culture of organization, discipline, motivation, commitmen and job performance.